Pemberdayaan Narapidana dalam Pembentukan Karakter dan Kemandirian di Lapas Kelas IIA Sorong melalui Pendidikan Kewarganegaraan: Pemberdayaan Narapidana, Karakter, Kemandirian - Arie Purnomo; Salmawati Salmawati; Wahyudin Halik; Sattu Sattu; Uswatul Mardliyah (LP3M Universitas Muhammadiyah Sorong, 2023)
Empowering inmates is an action taken to help them acquire independence and form positive characters. Citizenship education in prisons is one of the empowerment programs that can help inmates achieve these goals. Citizenship education in prisons is carried out by providing material on the rights and obligations as citizens, as well as national values. Citizenship education provides opportunities for inmates to improve their knowledge, skills, and positive attitudes in community life. The purpose of this research is to determine the effectiveness of empowering inmates through citizenship education in forming character and independence in prisons. The method used in this research is a qualitative method with data collection techniques through interviews, observation, and documentary studies. The results showed that citizenship education provided in prisons has a positive influence on the formation of character and independence of inmates. Inmates who participate in citizenship education programs in prisons have knowledge, skills, and positive attitudes that can help them in community life after being released from prison. Therefore, citizenship education in prisons needs to be continuously improved and expanded to achieve more effective inmate empowerment goals.